Procedimentos jurídicos para estruturação de concessão de infraestrutura e o desenvolvimento brasileiro - Gabriel, Yasser Reis (2016)
Brazil’s economic development depends on the expansion of public infrastructure, which in the last decades has been done through concession programs. The study aims to understand why the government has constantly resorted to 'permit studies' trough the administrative authorization referred in art. 21 of law 8.987/95 for obtain private assistance in structuring infrastructure concession projects. The suspicion is that it does as a way to replace the hiring of consulting services and avoid limitations of public procurement’s general system: law 8.666/93. To achieve this goal, it proposes to understand how each concession structuring procedure occurs: the contracted structuring and the authorized structuring. And through this, understand its advantages and limitations. The study found out that, given the particularities of consulting services for the structuring of concession, law 8.666/93 does not have adequate arrangements to fit this kind of contract. It also found out that the administration repeatedly seeks legal alternatives for contracting such services. It verified that the referred administrative authorization is currently used as one of these legal alternatives, despite not being created for this purpose. But still it does not meet the needs of public administration in the pursuit of getting infrastructure concession projects. Finally, it concludes that, ideally, the Brazilian legal system needs to establish a different regime to hire consultants to assist the administration in structuring infrastructure concession.